HUBUNGAN PENGETAHUAN DAN SIKAP SISWA SEKOLAH DASAR TENTANG SANITASI DASAR DENGAN TINDAKAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DI SD NEGERI 046579 DESA LAU PERANGGUNEN KAB.KARO - rio ferdi yuandra; Cintya Nathasa Br Ginting (Jurnal Penelitian Kesmasy, 2020)
Sanitation is defined as a public health effort that focuses on the control of various environmental factors,that effected to human health. Clean and Healthy Behavior (PHBS) is a set of behavior that is practiced on the basis of consciousness as a result of learning that makes a person or family can help their healthy life themselves. Based on that statement, the aim of this research is to see the correlation between knowledge and Attitudes about Basic Sanitation Behavior Clean and Healthy (PHBS).This type of research is a type of quantitative research with an observational method using a cross sectional approach with a population of all students in class IV, V, and VI who are in SD Negeri 046579 in Lau Peranggunen Kab.Karo, which is 82 people. The sample in this study is a total sampling technique. Based on the instruments in this study are questionnaires, data analysis techniques used the chi-square statistical test. Based on the chi-square analysis, it was found that there was a relationship between knowledge and attitudes of elementary school students with PHBS actions which amounted to (p = 0.046), there was a significant relationship between knowledge with PHBS actions. and the relationship between basic sanitation attitudes and PHBS actions were obtained as basic (p = 0.040), there was a significant relationship between PHBS attitudes and actions. Lau Kab karo residents to increase the knowledge, attitudes and actions of PHBS in the school environment in the teaching and learning process so that they understand and know the benefits for themselves and their environment.